Policy renewal of Indonesian mineral and coal smelters for Global Impact - Fitri, M. Fadly; Nyoman N, I; Suhartono, Slamet; Budiarsih, Budiarsih (Technium Social Sciences Journal, 2022)
This research is normative law. The rule of law gives the highest supremacy to a country in providing welfare and forming legal norms, the ratification of GATT through Law No.7 of 1994 concerning Ratification of the Agreement Establishing The World Trade Organization (ADDITIONAL TO STATE GAZETTE OF THE REPUBLIC OF INDONESIA NO. 3564) is the rule of law that has the highest supremacy, the result is to comply with the ratified GATT legal norms where the related parties of the public contract agreement can exercise the right to test for inconsistencies.